The influence of prosthetic foot types and altered sensory conditions on the postural stability of below-knee amputees during upright standing / Nooranida Arifin - Nooranida, Arifin (2016)

(untitled)
For individuals with below-knee amputation, the loss of the biological ankle joint and associated musculatures may adversely affect amputees’ ability to maintain upright posture successfully, particularly in altered sensory conditions. While postural stability performance among below-knee amputees has been explored, no research to date has systematically evaluated postural stability with different prosthetic foot types and modified sensory input. This research primarily aims to systematically evaluate the control of postural stability during primary sensory modifications among below-knee prosthesis users when wearing different types of prosthetic feet. This research also demonstrates the possibility of objective quantification of postural stability in below-knee amputees obtained from a commercially available computed posturography device. The mechanical properties of solid ankle cushioned heel (SACH) foot, single axis (SA) foot and energy storage and release (ESAR) Talux® foot were tested using a universal tensile machine. The intrarater test-retest reliability of static and dynamic postural stability indexes measurement using the Biodex® Balance System (BBS) was performed on 20 able-bodied participants. 19 participants (ten below-knee amputees and nine controls) took part in several studies including postural stability assessment of upright standing during visual, somatosensory and vestibular sensory modifications while wearing three different prosthetic types. Participants were asked to stand quietly with eyes-closed, on different surfaces (rigid, unstable and compliant) and with head tilting backward to simulate modified visual, proprioception and vestibular sensory input, respectively. The mechanical testing results showed that the ESAR foot had the lowest heel stiffness followed by SACH and SA. Similarly, the forefoot stiffness was the lowest for ESAR foot while SACH and SA had similar forefoot stiffness. The reliability results indicated that postural stability assessment using the BBS provides ‘good to excellent’ test-retest reliability over a one-week time interval. The findings v from the posturography assessment suggested that postural stability in below-knee amputees during quiet upright standing was not affected by the prosthetic foot factor, but was significantly affected when one of the primary sensory inputs was altered. When visual cues were absent, overall stability was reduced in SACH and ESAR feet, medio-lateral stability was reduced in SACH foot while anterior-posterior stability was reduced in ESAR foot. Standing on a compliant surface was demonstrated to significantly reduce the overall stability in SACH foot compared to that of an ESAR foot. Additionally, this study revealed that the differences between amputees and able-bodied participants can be distinguished when standing on a compliant surface. During vestibular sensory modification, postural instability in medial-lateral direction was significantly greater in all prosthetic feet compared to able-bodied individuals. From the time domain data, the loading time percentage on amputees’ intact limb was significantly longer than the amputated limb in all sensory conditions for all three prosthetic feet. The amputees also had a significant strong positive relationship between overall and medio-lateral stability indexes with all prosthetic feet types and altered sensory conditions. The analysis of Activities-specific Balance Confidence (ABC) score demonstrated a significantly higher score in ESAR compared to SACH and SA. In conclusion, the novel results presented in this thesis have important implications for amputee rehabilitation program and encourage an evidence-based practice during amputee assessment. These include identifying postural stability responses towards different sensory modifications and how these changes can be quantified and monitored using a reliable and practical computed posturography device